2010
DOI: 10.1038/jcbfm.2010.212
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Diffusion Tensor Imaging and Neuropathological Correlation in a Murine Model of Hypoxia–Ischemia-Induced Thrombotic Stroke

Abstract: Diffusion tensor imaging (DTI) is a powerful method to visualize white matter, but its use in patients with acute stroke remains limited because of the lack of corresponding histologic information. In this study, we addressed this issue using a hypoxia-ischemia (HI)-induced thrombotic model of stroke in adult mice. At 6, 15, and 24 hours after injury, animals were divided into three groups for (1) in vivo T2-and diffusion-weighted magnetic resonance imaging, followed by histochemistry, (2) ex vivo DTI and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 38 publications
6
56
0
Order By: Relevance
“…7 Other pathological changes in ischemic WM include segmental swelling of myelinated axons and the formation of spaces or vacuoles between the myelin sheath and axolemma ( Figure 1). 7,8 These observations confirm that WM is vulnerable to ischemia and that this insult damages oligodendrocytes, myelin, and axons in a manner that can proceed independently from neuronal perikaryal injury. In fact, up to 25% of ischemic strokes in humans are of the lacunar variety and are confined to WM areas such as the internal capsule.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…7 Other pathological changes in ischemic WM include segmental swelling of myelinated axons and the formation of spaces or vacuoles between the myelin sheath and axolemma ( Figure 1). 7,8 These observations confirm that WM is vulnerable to ischemia and that this insult damages oligodendrocytes, myelin, and axons in a manner that can proceed independently from neuronal perikaryal injury. In fact, up to 25% of ischemic strokes in humans are of the lacunar variety and are confined to WM areas such as the internal capsule.…”
supporting
confidence: 67%
“…When exposed to hypoxia or ischemia, these cells exhibit robust production of superoxide radical, lipid peroxidation, and conversion of iron stores to the oxidizing agent, ferrous ion. 8 The antioxidant ebselen significantly reduces axonal and oligodendrocyte damage as well as the neurological deficit associated with transient ischemia when administered 2 hours after the onset of stroke. 27 More antioxidants should be tested in models of pure WM ischemia to gain deeper insight into the therapeutic potential of this class of compounds.…”
Section: +mentioning
confidence: 99%
“…Table 4 describes the results of DTI and MTI in various settings and disease entities. Animal models and postmortem studies indicate that increased fractional anisotropy and mean diffusivity derived from DTI and magnetization transfer ratio from MTI correlate with axonal loss, demyelination and dentritic injury [29,36,70,76]. A recent study in hypoperfused mice is of particular interest as it examined the complementary value of DTI and MTI measures for delineation of white matter damage [36].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 99%
“…Animal models and postmortem studies indicate that quantitative DTI and MTI measures correlate with markers of myelin integrity, and axonal damage and density. [65][66][67][68] A study in brain hypoperfused mice examined the complementary value of DTI and MTI measures for delineation of white matter damage. 68 After continuous moderate hypoperfusion over 1 month the authors found that the reduction in fractional anisotropy paralleled a decrease in magnetization transfer ratio in several tissue compartments.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%